Identification of androgen receptor variants in testis from humans and other vertebrates. (26th June 2012) - Laurentino, S. S.; Pinto, P. I. S.; Tomás, J.; Cavaco, J. E.; Sousa, M.; Barros, A.; Power, D. M.; Canário, A. V. M.; Socorro, S.
Summary The androgen receptor (AR) is a ligand‐activated transcription factor member of the nuclear receptor superfamily. The existence of alternatively spliced variants is well recognised for several members of this superfamily, most of them having functional importance. For example, several testicular oestrogen receptor variants have been suggested to play a role in the regulation of spermatogenesis. However, information on AR variants is mostly related to cancer and androgen insensitivity syndrome (AIS) cases. The objective of this study was to investigate the expression of AR variants in the testis from humans and other vertebrates. Four AR variants [ARΔ2Stop, ARΔ223Stop, ARΔ3 and ARΔ4(120)] were identified in human testis. ARΔ2Stop and ARΔ3, with exon 2 or 3 deleted, respectively, were also expressed in human liver, lung, kidney and heart. In addition, ARΔ2Stop was expressed in rat and gilthead seabream testis, while an ARΔ3 was detected in African clawed frog testis. This is the first report revealing the existence of AR variants in the testis of evolutionarily distant vertebrate species and in nonpathological tissues. These data suggest the functional importance of these novel AR forms and demonstrate a complexity in AR signalling that is not exclusive of pathological conditions.